2018
DOI: 10.1007/s12035-018-1317-0
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Restores Ganglioside Homeostasis and Improves Pathological and Behavioral Outcomes Post-stroke in the Rat

Abstract: Perturbations of ganglioside homeostasis have been observed following stroke whereby toxic simple gangliosides GM2 and GM3 accumulate, while protective complex species GM1 and GD1 are reduced. Thus, there is a need for therapeutic interventions which can prevent ganglioside dysregulation after stroke. A pharmacological intervention using chloroquine was selected for its transient lysosomotropic properties which disrupt the activity of catabolic ganglioside enzymes. Chloroquine was administered both in vitro (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The authors of this study proposed that the shift from complex to simple gangliosides might be due to the catabolism of complex gangliosides with accumulation of deriving GM2 and GM3 in the lysosomes (Whitehead et al, 2011). In support of this hypothesis, administration of chloroquine in rats, prior to and after stroke, to block ganglioside catabolism, prevented the shift from complex to simple gangliosides as well as motor deficits, decreased inflammation and increased cell survival at the injury site (Caughlin et al, 2019). These data suggest that the depletion of complex gangliosides due to their catabolism might contribute to tissue damage in stroke models and that increasing endogenous ganglioside synthesis might have beneficial effects.…”
Section: Strokementioning
confidence: 66%
“…The authors of this study proposed that the shift from complex to simple gangliosides might be due to the catabolism of complex gangliosides with accumulation of deriving GM2 and GM3 in the lysosomes (Whitehead et al, 2011). In support of this hypothesis, administration of chloroquine in rats, prior to and after stroke, to block ganglioside catabolism, prevented the shift from complex to simple gangliosides as well as motor deficits, decreased inflammation and increased cell survival at the injury site (Caughlin et al, 2019). These data suggest that the depletion of complex gangliosides due to their catabolism might contribute to tissue damage in stroke models and that increasing endogenous ganglioside synthesis might have beneficial effects.…”
Section: Strokementioning
confidence: 66%
“…2,22 CQ is best known as an antimalarial drug, which has been demonstrated to have good application value and therapeutic potential in various animal models of neurological disorders. [12][13][14]23 Furthermore, no obvious adverse events or reproductive toxicity were found after CQ intervention in the animal experiments and clinical patients. 11 Herein, to some extent, we believe that CQ will be a safe therapeutic option for HIBD in neonates due to its peculiarity of low toxicity and well-tolerated therapy.…”
Section: Discussionmentioning
confidence: 85%
“…Second, CQ had been identified to protect BBB integrity and prevent neuronal cell death in newborn rats after HIBD. Interestingly, CQ possessed anti-inflammatory properties in CNS diseases, , and whether or not CQ treatment protects the neurovascular unit (NVU) in neonatal HIBD by regulating neuroinflammation should be further studied. Furthermore, hypothermia is already considered as the standard therapy for neonatal hypoxic-ischemic encephalopathy (HIE), but it is not universally successful .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chloroquine, an established drug originally used for the treatment of malaria, has been reported to have anti-inflammatory and immunomodulatory properties ( Silva et al, 2021 ). Recently, several studies have shown that chloroquine pretreatment can alleviate brain injury in IS through a variety of mechanisms, including the inhibition of the inflammatory response by lowering myeloperoxidase activity and inflammatory cytokine gene expression ( Cui et al, 2013 ; Zhang Y. P. et al, 2020 ) and alleviation of neuronal injury by restoring ganglioside homeostasis ( Caughlin et al, 2019 ). Gabriel et al (2014) reported that chloroquine can effectively increase Gpnmb transcription in mice as a lysosomal stress inducer.…”
Section: Discussionmentioning
confidence: 99%